PENGARUH PERSEPSI KEMUDAHAN KEPERCAYAAN DAN RISIKO TERHADAP MINAT BELANJA KONSUMEN MUSLIM PADA APLIKASI E COMMERCE DI MASA PANDEMI (STUDI KASUS PADA PENGGUNA SHOPEE KOTA MALANG) - Rifatul Waasiah; Dwiyani Sudaryanti; Junaidi Junaidi (El-Aswaq: Islamic Economics and Finance Journal, 2022)
The Internet is something of an invention that has had a huge impact onsociety. The development of the internet today is very advanced and itsdistribution is also very wide and unlimited. The benefits of the internet are notonly felt by individuals, but millions of people around the world are involved inthe benefits of the internet. One area that has benefited greatly from the internetis economics. The benefits of the internet provide many conveniences for variousaspects of business activities. The application of information technology has animportant role for companies that have benefits, among others, to gaincompetitive advantage with the strategies they have. Not only that, informationtechnology has become a basic need for an industry to carry out almost allbusiness activities